The Effect of a Problem Centered Learning on Student’s Mathematical Critical Thinking - Lidya Putri Apriliana; Isnaini Handayani; Subhan Ajiz Awalludin (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2019)
Since Indonesian students’ critical thinking skills in junior high school is still in unexpected level, it should be improved through teaching and learning process. The objective of the study is finding out the influence of problem centered learning approach toward students’ mathematical critical thinking ability. Every student should have mathematical critical thinking skills to make mathematics lessons are easier. Using the critical thinking skills will help students improving problem solving skills. However, the current critical thinking ability of junior high school students is still low. This research used quasi experimental design with Static Group Comparation type. The research sample consisted of two classes with each class of 35 students. The research instrument consists of six questions which indicate a mathematical critical thinking ability. Data analysis of this study used the Mann-Whitney test. The results of the study indicate that there is an effect of the problem-centered learning approach on the students' mathematical critical thinking ability with testing criteria is high.